Study on the effect of ultrasound on cellulose hydrolysis by cellulase - Siti Hajar , Zerry @ Azhari (2013)
Cellulose is a natural polymer that has a potential of utilization of cellulosic biomass as a renewable resource for reducing emissions of carbon dioxide and to be used as future fuis :such as ethanol and other chemical products. The study on the effect of ultrasound on cellulose hydrolysis by cellulase was to be conducted. The purpose of the study is to determine the optimum condition of sonication regimen in enzymatic hydrolysis of cellulose, determine the best parameters of sonication powers and duty cycle for enzymatic hydrolysis using Michaelis-Menten kinetics and study the effect of substrate particle size (sigmacell cellulose) on the rate of reaction (solid liquid mass transfer effect). The method of this research include the preparation of substrate by dissolving the powder in 500m1 of 0.05 M acetate buffer, pH 4.8, hydrolysis of cellulose in a 2 L stirred beaker, sonication amplitude for ultrasound-assisted hydrolysis, testing the cellulase stability and activity, and also Dinitrosalicylic Acid (DNS) method for analysis. From the experiment, it can be conclude that both hydrolysis of soluble and insoluble cellulose followed Michealis Menten kinetics model. Besides that, it is proved that sonication always enhances rate of product formation regardless of substrate particle size. In contrast, an increasing particle size reduced the rate of hydrolysis regardless of implied sonication.